Bentuk Pengaturan Perbankan Digital di Negara Indonesia dan Singapura - Sudirman, Lu; Disemadi, Hari Sutra; Jerryen, Jerryen (Legal Spirit, 2024)
Technological developments and digital transformation have had a significant impact on the banking industry sector, triggering the rapid growth of digital banking. This research aims to examine the regulation of digital banking in the era of digital banking transformation by focusing on the comparison between Indonesia and Singapore. This research uses normative juridical research with a statute approach and comparative approach. The results of this research provide in-depth insight into the differences and similarities in regulatory approaches to the level of security, innovation and digital banking penetration between Indonesia and Singapore. The results of this research bring a comprehensive understanding of how the two countries respond to the challenges and opportunities in the era of digital banking transformation which is expected to contribute to the development of digital banking in Indonesia today.